Urdu ka guldasta revised edition "Kanwal" (For Class 8) - Fouzia ahsan farooqui (Oxford University Press; Pakistan, 2022)
Kanwal Class 8 is an educational textbook that offers a diverse range of lessons, activities, and stories to support the academic development of eighth-grade students.